2015
DOI: 10.1038/npp.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β3 Haploinsufficiency Modulates Serotonin Transport and Antidepressant-Sensitive Behavior in Mice

Abstract: Converging lines of evidence have identified genetic interactions between the serotonin transporter (SERT) gene and ITGB3, which encodes the β3 subunit that forms the αIIbβ3 and αvβ3 integrin receptor complexes. Here we examine the consequences of haploinsufficiency in the mouse integrin β3 subunit gene (Itgb3) on SERT function and selective 5-hydroxytryptamine (5-HT) reuptake inhibitor (SSRI) effectiveness in vivo. Biochemical fractionation studies and immunofluorescent staining of murine brain slices reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Also in family 10001, seven affected, and one unaffected sibling, share the segment on chromosome 17q21.32 containing integrin subunit beta 3 ( ITGB3 ), which has been previously associated with ASD [4653], although not in a cohort of Irish ASD cases [54]. Considered by ASD@Princeton to be a known ASD gene, ITGB3 plays a role in cell adhesion, and regulates serotonin levels through an interaction with the serotonin transporter [55]. Interestingly, the lone affected case that does not share this segment is the MZ twin.…”
Section: Discussionmentioning
confidence: 99%
“…Also in family 10001, seven affected, and one unaffected sibling, share the segment on chromosome 17q21.32 containing integrin subunit beta 3 ( ITGB3 ), which has been previously associated with ASD [4653], although not in a cohort of Irish ASD cases [54]. Considered by ASD@Princeton to be a known ASD gene, ITGB3 plays a role in cell adhesion, and regulates serotonin levels through an interaction with the serotonin transporter [55]. Interestingly, the lone affected case that does not share this segment is the MZ twin.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin β3 influences synaptic plasticity via AMPA and NMDA receptor trafficking mechanisms ( Bahr, 2000 , Bernard-Trifilo et al., 2005 , Cingolani et al., 2008 , Juhasz et al., 2008 , Lin et al., 2003 , Pozo et al., 2012 ), which are involved in the functional and structural alterations observed after exposure to chronic stress ( Christian et al., 2011 , Kallarackal et al., 2013 ). Integrin β3 also influences midbrain high-affinity 5-HT reuptake via the serotonin transporter (SERT) ( Mazalouskas et al., 2015 , Whyte et al., 2014 ), and mice lacking SERTs display enhanced sensitivity to repeated stress, which are associated with altered dendritic morphology of pyramidal neurons in the prefrontal cortex ( Wellman et al., 2007 ). Our neurochemical studies revealed increased midbrain levels of 5-HT and its metabolite, 5-HIAA, in mice lacking β3 expression, which were not influenced by UCMS.…”
Section: Discussionmentioning
confidence: 99%
“…Cell adhesion molecules, such as integrins, are ideally poised to regulate many of these processes, as many are involved in apoptosis, dendritic reorganization, the regulation of synaptic connectivity, and receptor localization ( Kerrisk and Koleske, 2013 , Scheiffele et al., 2000 ). Integrins are particularly enriched in synaptic regions ( Bahr et al., 1997 , Kramar et al., 2002 , Mazalouskas et al., 2015 , Nishimura et al., 1998 ), where they participate in synaptic development, maintenance and the cytoskeletal rearrangements that accompany synaptic activity ( Bahr, 2000 , Chavis and Westbrook, 2001 , Hama et al., 2004 , Karanian et al., 2005 , Nikonenko et al., 2003 ). Integrin expression and downstream signaling are modulated by antidepressant exposure, implying that integrins are involved in mood regulation ( Malki et al., 2012 , Oved et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten days post-infection, cultures were fixed for 8 min with 4% PFA/4% sucrose at room temperature (RT), treated for 10 min at 50°C with a sodium citrate solution (10 mM tri-sodium citrate dihydrate, pH 6.0, 0.05% Tween-20) to retrieve the β3 integrin antigen (Mazalouskas et al, 2015) and permeabilized for 10 min at RT with 0.1% TritonX-100. β3 integrin staining was revealed using a rabbit monoclonal anti-integrin β3 (1: Ai,coloc is calculated as ∑i Ai but only for pixels where also the second channel B is above threshold).…”
Section: Rna Extraction and Rt-qpcrmentioning
confidence: 99%